Evaluation of the genotoxic potential of graphene nanomaterials - Teixeira, Bruna Sofia Carvalho (2019)
Graphene is a purely carbon-based, honeycomb-structured, one-atom thick layer of carbon atoms, bonded to another by sp2 hybridization and since its isolation, its unique properties such as high surface area, electrical and thermal conductivities have been widely studied. Graphene and graphene-based nanomaterials are now applied in several fields, as for instance medicine, electronics, sensors and environment. Despite the wide application of graphene nanomaterials, the information on the risks to human health and the environment are not yet well known. Consequently, it is important to investigate and evaluate the potential toxicity of graphene. This thesis revises the applications and toxicity of Graphene-Family Nanomaterials (GFNs) to human cells. Also, the assays for in vitro evaluation of genotoxic effects were also shortly revised. The relevance of the evaluation of potential genotoxic effects of GFNs is highlighted in this thesis.